Intraoperative PH neutralization after nasal button battery removal in children: A case report - See Hui Chiu; Lynn Huiting Koh; Jenica Su-Ern Yong (Otolaryngology Case Reports, 2021)
We present 2 pediatric patients with impacted nasal button battery who underwent emergency examination under anesthesia and removal of nasal BB followed by intraoperative pH-neutralization nasal irrigation with 50–100 ml of 0.25% acetic acid. Although a pH-neutralization mitigation strategy has been utilized in patients with impacted esophageal button battery, it has never been utilized in patients with impacted nasal button battery. This is the first report to our knowledge of intraoperative pH-neutralization with acetic acid nasal irrigation following removal of nasal button battery.